Reproductive biology of the southern pufferfish, Sphoeroides nephelus (Actinopterygii: Tetraodontiformes: Tetraodontidae), in the northern coast off the Yucatan Peninsula, Mexico - J.C. Peniche-Pérez; C. González-Salas; H. Villegas-Hernández; R. Díaz-Gamboa; A. Aguilar-Perera; S. Guillen-Hernández; G.R. Poot-López (Acta Ichthyologica et Piscatoria, 2019)
Background. Overexploitation of fishery resources has led to the capture of alternative species of a lower trophic level, considered previously unprofitable or unfit for human consumption. The southern pufferfish, Sphoeroides nephelus (Goode et Bean, 1882), is a bycatch species of the recreational fishery in the USA and Mexico. Unlike other species of the genus Sphoeroides, there is no background on their reproductive cycle. Therefore, this study aimed to describe several reproductive traits (sex ratio, gonadal development, annual reproductive cycle, and fecundity) of specimens from the northern coast of the Yucatan Peninsula, Mexico. This kind of information might serve as a point of reference for its potential use either in the pharmaceutical industry, aquarium trade, as well as in aquaculture. Materials and methods. The reproductive biology of the southern pufferfish was described based on 189 females and 223 males, caught off the northern coast off the Yucatan, Mexico, during an annual cycle. Several reproductive traits, such as the annual cycle of gonad development, sex ratio, and the batch fecundity were determined. Results. The sex ratio showed no significant difference from 1 ÷ 1 ratio. Male’s reproductive season lasted from August to May, although females were spawning from August to April. The size at 50% maturity was estimated at 14.93 cm TL for females. Batch fecundity ranged between 59 087 and 367 022 oocytes (mean 176 456) per spawning batch, and it was significantly fitted to both female size and weight based on power and linear regression models, respectively. The relative batch fecundity was estimated at 828 ± 182 oocytes per gram of eviscerated weight, and 11 989 ± 4774 oocytes per gram of gonad weight. Conclusion. It was determined that S. nephelus exhibited 1 ÷ 1 sex ratio, an asynchronous development of oocytes and indeterminate fecundity with batch spawning. The species has a protracted reproductive season that lasted almost all year round with peaks in February–March (before of the dry season) and a brief inactive period in June–July (before of the wet season). This latter information should be helpful to obtain a broodstock that would be the base to produce fingerlings to be raised, instead of collecting individuals from the wild.